2017 Pacific Standard Time: LA/LA - "The Latino Museum of History, Art and Culture (1995-2000) Revisited"
Wall created for the 2017 Pacific Standard Time LA/LA "The Latino Museum of History, Art and Culture (1995-2000) Revisited exhibit at Napa Hall at CSU Channel Islands.